Evaluating the Potential Use of Tidal Energy: A Study of Different Regions in Kuwait - Alshatti, Saad Abdullah; Alsubai'e, Mohammed Salem (Engineering International, 2018)
This Study is based on Statistical Data of Tidal Waves in the Different Regions of Kuwait. Nowadays, Kuwait city is considered a good example for the countries that characterizes with an essential rate of exhaustion of energy. This in turns results in a substantial increase with need of immaculate and renewable energy obstetrics origins that can be used in generating electricity. This Paper aims to estimate the possibility for employing tidal energy in Kuwait city according to statistically collected data about tidal waves in several areas. Statistics associated to current velocity of water were gathered from Kuwait Institute for Scientific Research. Additionally, Civil Aviation Meteorological Department was managed to be appropriate for obtaining information about current velocity of water. The obtained results in this paper showed that there is a great possibility to use resources of renewable within Kuwait to achieve the demands of energy. Also, the results shows that Plants of tidal power are built within different locations, and the MENA area still lacks to tidal power plant, where that the lone reported plant of the power via tides is the that reputable through an Israeli company called WERPO.
Keywords: Kuwait; Renewable Energy; Current Velocity; Tidal Energy; Tidal Plant; MENA Region; Tidal Waves